A comparative investigation into the influence of the constitutive model on the prediction of in-plane formability for Nakazima and Marciniak tests. (November 2019) - Noder, J.; Butcher, C.
Highlights: Consid è re criterion must be enforced in the calibration of the hardening law. The hardening rate can significantly influence the Nakazima FLC process-corrections. Shear tests are a viable alternative to bulge tests for the hardening response to large strains. In-plane formability can be accurately predicted using the MMFC model without calibration. Abstract: The present study investigates the use of both Marciniak and Nakazima tests to generate the forming limit curves (FLCs) for a power-law hardening dual phase steel, DP980, and an aluminum-magnesium alloy, AA5182, that exhibits dynamic hardening and saturation-type behavior. The recently proposed methodology of Min et al. (2016) to compensate for the so-called process effects of non-linear strain paths (NLSP) and contact pressure was evaluated and applied to the Nakazima FLCs to enable comparison with the Marciniak FLCs and the formability predictions of the Modified Maximum Force Criterion (MMFC) of Hora et al. (1994, 2013) for in-plane stretching. An emphasis was placed upon the experimental determination of the constitutive model to plastic strains in excess of 0.5 using tensile and shear tests. A flexible variant of the Hockett-Sherby (1975) hardening model for large strain levels along with constraints upon the hardening model calibration are proposed. It is demonstrated that the choice of hardening model, test data, and the calibration procedure can have a marked influence on the Nakazima process corrections and the predicted FLC using the MMFC model. An extension to the Linear Best Fit (LBF) limit strain detection methodology by Volk and Hora (2011) was developed to account for bend severity and the material hardening response and is compared with the ISO 12004-2 limit strains. If the hardening model is accurately calibrated to large strain levels, the analytical MMFC predictions were in excellent agreement with the process-corrected Nakazima and Marciniak FLCs for DP980. The results for the AA5182 were found to be strongly dependent upon the choice of hardening model that influences both the MMFC and the contact pressure correction.